Pembaruan Standar serta Peningkatan Efektivitas dan Efisiensi Proses Loading Unit dengan Simulasi Flexsim - Richie Ruslim; I Nyoman Sutapa (Jurnal Titra, 2020)
This research was done at a market leader for motorcycle providers. In implementation of distribution there is standard where there are some parts of existing standard that are less relevant to current conditions. In addition, the observations made show that the truck queues are quite dense because the loading process is less effective and efficient. To solve this problem, simulation model was made then looked at the results of several proposals before applying them. The first proposal is to increase worker utilization by adding final checking process to ensure the quality of the units. The results obtained are the output produced is not significantly different from the initial model and the existence of proposed standard update with the final checking process. The second proposal is to make dedicated location, so the distance is reduced. The results obtained from this proposal are the process of moving units to become more effective and efficient and the output of units and trucks increased. The third proposal made is to speed up the loading unit setup to be more effective and efficient. From this proposal, we obtain significantly different results from the initial model in which the number of trucks and units output increased.